Evaluation of Accountability in The Performance Report of The Batam Free Trade and Free Port Authority (bp Batam) - Syuzairi, Muhammad; Sofia, Myrna; Salim, Dwi Fitrizal (Journal of Ecohumanism, 2024)
This research aims to analyze and evaluate the evaluation process of the Performance Accountability Report of the Batam Free Trade and Free Port Authority (BP Batam) based on results in 2022. This study focuses on evaluating the performance of BP Batam using qualitative research methods. Data collection is carried out through secondary data from planning documents and financial and performance reports of government agencies. Data analysis is conducted using techniques such as thematic analysis, grounded theory, or narrative analysis. The results of this research indicate that there are challenges in the performance planning of the BP Batam Government, such as inconsistencies between performance planning in documents such as RPJMD, RENSTRA SKPD, RKT, TAPKIN, and LAKIP, which are caused by a lack of coordination among various stakeholders and unexpected policy changes. The performance measurement process of BP Batam has not been optimally utilized for control and monitoring. BP Batam needs to establish good internal coordination among its units, implement an effective monitoring and evaluation system, and optimize its human resources to overcome challenges in the preparation of LAKIP. BP Batam can use the combination of the Performance Blueprint and Friedman's Four Quadrant Approach for measuring and managing organizational performance more effectively.